A Study on Coloring Properties of Rheum emodi on Jute Union Fabrics. (11th February 2014) - Nayak, Lopamudra
Abstract : Jute-cotton and jute-wool union fabrics have been printed with colorant extracted from Rheum emodi with guar gum and albumin as thickening agents and aluminium sulphate, copper sulphate, and ferrous sulphate as mordants. Printing with Rheum emodi colorant with different mordants resulted in different shades ranging from yellowish brown, deep brown, reddish brown, and gray shades to olive black. The K/S value showed that mordants, namely, CuSO4 and FeSO4, exhibited high colour absorption regardless of the nature of material used. All the printed samples have good to excellent wash, rubbing and light fastness properties regardless of the nature of materials, mordants, and thickeners used. Guar gum is closely at par with albumin as a thickening agent and considering the cost and availability of raw material, guar gum is the better choice for the textile industry.